Islamic Character Formation in Contrasting Cultures: A Case Study of NU and Muhammadiyah Boarding Schools - Aziz, Akbar Nur; Rahmatullah, Azam Syukur; Azhar, Muhammad; Sairin, Sjafri (LPPM IAIN Kudus, 2026)
This study aims to analyze and compare the formation of religious identity, the internalization of values, and students' spiritual attitudes in NU and Muhammadiyah boarding schools. This study uses a qualitative approach with an exploratory case study design. Data collection techniques included in-depth interviews, participatory observation, and document analysis. Data were analyzed using pattern-matching strategies based on cross-cultural psychology theories (Hofstede, Berry, and Tajfel). The results showed that the NU shapes students' values and character through internalization of symbols, traditions, and spiritual relationships. In contrast, the Muhammadiyah pesantren instills values through rational, structural, and discursive approaches. The religious identity of NU students is inclusive and communal, while Muhammadiyah students show normative and argumentative identities. These findings emphasize that the Nusantara Islam and Progressive Islam models are not only an ideological narrative, but also function as a cultural framework that shapes the psychological structure of students. This study contributes to understanding how cultural frameworks within Islamic boarding schools shape the psychological construction of religious identity, offering an integrative perspective on the relationship between educational culture and faith development. However, this research is limited to two case study sites and qualitative data; thus, further comparative studies with broader samples and quantitative or mixed-methods designs are recommended to deepen these findings.